Corporate accelerators: design and startup performance - Nikolaus Seitz; Erik E. Lehmann; Patrick Haslanger (Small Business Economics, 2023)
Corporate accelerators (CAs) have emerged as a key component of entrepreneurship ecosystems, offering startups corporate guidance, industry connections, and resources for accelerated venture creation. Although their proliferation is evident, we still know little about the value they produce for startups across different contexts. This study investigates the organizational setup and program design of 15 CAs in Germany using a unique and hand-collected dataset of 223 alumni startups. Our findings reveal a tradeoff: Specialized and integrated programs positively impact startups' speed to market and growth, while specialization and rising corporate control may hinder follow-up venture capital financing. This research contributes to our understanding of CAs and the startup acceleration process and provides insights for corporate and accelerator managers and startups alike. Startups can use these findings to identify the most suitable CA for their needs. Program managers and designers gain insights into the strategic orientation and organizational setup that positively impact startup acceleration.
Keywords: G32; G24; L25; L26; M13; M21; 330; Corporate accelerators; Startup support; Accelerated programs